The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/jmwh.13474
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Aversion Response (BAR): A Descriptive Study

Abstract: IntroductionFor many women, breastfeeding their infant is an enjoyable experience. Some, however, have reported negative sensations such as an overwhelming need to unlatch while breastfeeding. This phenomenon is known as breastfeeding aversion response (BAR). The incidence of BAR is unknown and literature on this experience is limited. This study therefore aimed to expand the understanding of BAR using an online survey targeting those who have experienced feelings of aversion while breastfeeding.MethodsAn onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…Possible treatment options and self-care strategies for BAR which have been found in previous research (Morns et al, 2023)…”
Section: Implications For Practice and Further Researchmentioning
confidence: 91%
See 4 more Smart Citations
“…Possible treatment options and self-care strategies for BAR which have been found in previous research (Morns et al, 2023)…”
Section: Implications For Practice and Further Researchmentioning
confidence: 91%
“…BAR is defined as feelings of aversion while breastfeeding for the entire time that the child is latched (Morns et al, 2021 ). Previous research on BAR has identified that breastfeeding with BAR feels tiring, exhausting and sickening (Morns et al, 2023 ). The in‐the‐moment sensations of BAR were described by those experiencing it as, ‘touched out, feeling violated, feeling angry, sad, dread, anxiety, guilt, worry, and feeling a disconnect between wanting to breastfeed and having negative feelings’ (Morns et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations